2016
DOI: 10.3389/fpsyt.2016.00140
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Medical Conditions and Negative Affect; Racial Variation in Reciprocal Associations Over Time

Abstract: BackgroundThe Black–White health paradox can be defined as lower frequency of depression despite higher prevalence of economic and social adversities as well as chronic medical conditions (CMC) among American Blacks compared to American Whites. Based on this paradox, the CMC – depressive symptoms link is expected to be weaker among Blacks than Whites. We conducted a 10-year longitudinal study to compare Blacks and Whites for bidirectional associations between number of CMC and negative affect over time.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 73 publications
5
44
0
Order By: Relevance
“…Our finding regarding larger effects of history of non-fatal physical assault on risk of mortality in Whites compared to Blacks agrees with other research showing risk and protective factors have stronger effects for Whites than Blacks [20,55], a pattern which is frequently shown for physical and mental health outcomes ( [9,[11][12][13][14][15][16][17][18][19][56][57][58][59][60][61]; see References [20,55] for a review). Stronger effects of low education [17], unemployment [12], poor neighborhood quality [11], depression [16,18,19,62,63], hostility and anger [64], low sense of self efficacy [14], and low perception of control over life [65] were shown for Whites than Blacks.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our finding regarding larger effects of history of non-fatal physical assault on risk of mortality in Whites compared to Blacks agrees with other research showing risk and protective factors have stronger effects for Whites than Blacks [20,55], a pattern which is frequently shown for physical and mental health outcomes ( [9,[11][12][13][14][15][16][17][18][19][56][57][58][59][60][61]; see References [20,55] for a review). Stronger effects of low education [17], unemployment [12], poor neighborhood quality [11], depression [16,18,19,62,63], hostility and anger [64], low sense of self efficacy [14], and low perception of control over life [65] were shown for Whites than Blacks.…”
Section: Discussionsupporting
confidence: 90%
“…Compared to their White counterparts who have not experienced the same level of adversities, one may hypothesize that Blacks may be more resilient to advertises such as non-fatal physical assault. This is in line with previous research showing weaker effects of social adversities for Blacks compared to Whites [9,[11][12][13][14][15][16][17][18][19].…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…According to our findings, SES differences in death from renal disease are not exclusively a result of SES gaps in exposures to medical risk factors (DM, HTN, and obesity). Instead, the same risk factors can have different roles across social groups, which is in line with the differential effect hypothesis. Thus, understanding the causal paths between social factors, medical risk factors, and health outcomes requires understanding the existing complex heterogeneity in the effects of the same risk factors on outcomes.…”
Section: Discussionmentioning
confidence: 84%
“…Similar differences have been found between Blacks and Whites (Johnson, 1989). In a series of studies, Assari has shown that depressive symptoms and negative affect better predict subsequent change in physical health outcomes such as chronic medical conditions and mortality for Whites than Blacks (Assari and Burgard, 2015; Assari et al, 2015b, 2016a,b; Assari and Lankarani, 2016b). …”
Section: Introductionmentioning
confidence: 99%